The first successful cochlear implant in Latin America after severe aminoglycoside-induced ototoxicity in a Peruvian patient cured of extensively drug-resistant tuberculosis - Pecho-Silva, Samuel (2023)
Introduction: Multidrug-resistant tuberculosis is a significant public health problem for which drugs are used with many adverse effects. Among the devastating consequences of these diseases, there is a wide variation in the incidence of ototoxicity and hearing loss in patients with multidrug-resistant and extremely resistant tuberculosis. Cochlear implants may be indicated in patients with unilateral/severe bilateral hearing loss with no benefit from conventional hearing aids, but their use in patients with tuberculosis is rare. Case report: We present the first case of a right unilateral cochlear implant performed on a 34-year-old Peruvian patient who presented profound sensorineural hearing loss of cochlear origin. Conclusion: Cochlear implant surgery is an essential milestone in the treatment of patients with auditory sequelae of tuberculosis treatment. Close monitoring of possible complications of tuberculosis treatment should be strengthened in countries with a high incidence of multidrug-resistant and extremely resistant tuberculosis.